2016
DOI: 10.1007/s11469-016-9721-z
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Awareness and Attitudes Regarding Adolescent Risk Behaviours: a Sample of Finnish Middle and High School Teachers

Abstract: Empirical evidence has shown that youth gamble on both regulated and unregulated games, despite legislative prohibitions. This study assesses middle and high school teachers’ awareness and attitudes regarding adolescent gambling and other potentially high-risk behaviours in Finland. A convenience sample of teachers (N = 157) from 13 provinces participated in the survey. The results suggest that teachers in Finland were more knowledgeable of the age limits of other adolescent high-risk behaviours than the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…This may reflect the lay perception of gambling as a harmless hobby (Campbell et al 2011), whereas professionals have a keener awareness of the potential problems involved. Our findings furthermore showed that professionals had gaps in their knowledge about problem gambling, but were interested in attending continuing education (Castrén et al 2017), which is in line with another Finnish study (Castrén et al 2016) and two studies from other countries (Derevensky et al 2013;Temcheff et al 2014). Our earlier work prompted greater interest among professionals in problem gambling and in continuing education in the form of tailored workshops with supportive materials (e.g., Hodgins and Makarchuk 2002).…”
supporting
confidence: 87%
“…This may reflect the lay perception of gambling as a harmless hobby (Campbell et al 2011), whereas professionals have a keener awareness of the potential problems involved. Our findings furthermore showed that professionals had gaps in their knowledge about problem gambling, but were interested in attending continuing education (Castrén et al 2017), which is in line with another Finnish study (Castrén et al 2016) and two studies from other countries (Derevensky et al 2013;Temcheff et al 2014). Our earlier work prompted greater interest among professionals in problem gambling and in continuing education in the form of tailored workshops with supportive materials (e.g., Hodgins and Makarchuk 2002).…”
supporting
confidence: 87%
“…Most teachers (over 70%) were aware of the legal age limit for online gambling, slot machine gambling, purchasing a lottery ticket, and casino gambling. 79 However, their awareness for gambling activities were not as accurate as their knowledge of other potentially risky activities, such as purchasing alcohol, purchasing cigarettes, or driving a car. 79 Teachers reported having observed students gambling (21.9%) and overheard students talking about gambling (43.8%).…”
Section: Awareness Of Legal Age Limitsmentioning
confidence: 99%
“…79 However, their awareness for gambling activities were not as accurate as their knowledge of other potentially risky activities, such as purchasing alcohol, purchasing cigarettes, or driving a car. 79 Teachers reported having observed students gambling (21.9%) and overheard students talking about gambling (43.8%). However, only 16.8% and 17.6% of the teachers correctly estimated the percentage of 11-to 14-year-old and 15-to 17-year-old-students, who had gambled in the past year.…”
Section: Awareness Of Legal Age Limitsmentioning
confidence: 99%
See 2 more Smart Citations